Analisis Faktor yang Memengaruhi Implementasi Pendidikan Cerdas dalam Sistem Pemerintahan Berbasis Elektronik - Wendy Nur Falaq; Dana Indra Sensuse (Fakultas Teknik Universitas Hamzanwadi, 2021)
The improvement of education in an area is determined by the government's method of managing its education system. Smart education is an implementation of e-Government in a learning system that uses 21st century skills with the support of IT infrastructure and implementing the latest technological innovations. The implementation of smart education is required, especially during the pandemic and post-pandemic to improve the quality of education which has declined since the beginning of covid-19 pandemic, but not all regions in Indonesia are able and ready to implement the concept. City/district governments, especially those that have implemented smart cities, need a reference regarding the factors that considered in implementing smart education to avoid the risk of failure. Based on these problems, the purpose of this study is to create a summary of the factors that need to be considered to increase the success of smart education implementation. This study uses a systematic literature review method to identify factors that are considered in implementing smart education based on previous studies. The research produces five main aspects which are a summary of all the factors found in previous studies, which consist of technological aspects, data aspects, human resources aspects, governance aspects, and financial aspects. All factors from these five aspects can be a reference for the government and related parties to increase the success rate of implementing smart education